Financial Performance Measurement of Companies in the BIST Sustainability 25 Index with LBWA and MEREC-based CRADIS Methods - Süreyya Yılmaz Özekenci (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractFinancial performance refers to the assessment of a firm’s capacity to generate profits and manage its financial assets effectively during a specific period of time. This study addresses the evaluation of financial performance of companies in the BIST Sustainability 25 Index using a hybrid MCDM method. For this investigation, nine criteria, namely, acid-test ratio, asset turnover, current ratio, debt ratio, EBITDA, net profit margin, return on equity, stock return and stock turnover are used to determine the financial performance of companies. In this study, the weight of criteria is calculated using both subjective (LBWA) and objective (MEREC) weighting approaches. After the weight of criteria is determined, the financial performance of companies is ranked using the CRADIS method. The results showed that EBITDA and Stock turnover are the most and least important criteria, respectively. According to results obtained from the CRADIS method, Ereğli Iron-Steel, Enka construction and Ford Otosan have the highest financial performance, while Vestel, Arçelik and Çimsa have the lowest financial performance in the period of 2018 and 2022. Additionally, the robustness and validity of the results are tested by various MCDM methods, namely, ARAS, COPRAS, EDAS, MABAC, MAIRCA, MARCOS, TOPSIS, CoCoSo and MAUT.